Keyword intelligence : keyword research for search, social, and beyond - Jones, Ron, 1956- (Serious skills., 2012)
A unique book on the art and science of keyword research Keyword research can make or break a marketing campaign, an optimization strategy, and pay-per-click ad campaigns. Written by a keyword research expert, this essential resource drills home the importance of targeting the right keywords or phrases in order to get traffic from search engines and social media channels. Author Ron Jones imparts his wisdom and experience for determining which keywords will work based on a searcher's intent and he shows you how to research social, mobile, and video marketing tools that can ultimately become the foundation of a marketing campaign.